2020
DOI: 10.3892/etm.2020.9247
|View full text |Cite
|
Sign up to set email alerts
|

Association between α1‑antitrypsin and acute coronary syndrome

Abstract: α1-antitrypsin (AAT) is a protein released as part of the anti-inflammatory response. It regulates the activity of serine proteinases and has a crucial role in the pathogenesis of acute coronary syndrome (ACS). The present study aimed to examine its role in patients with ACS. The plasma samples of 117 patients were collected at the Cardiology Department of the Affiliated Hospital of Youjiang Medical University (Baise, China). These included 46 cases of ACS (who met the diagnostic criteria for ACS and had ≥50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Many authors have also reported that inhibition of ERK pathway leads to amelioration of pulmonary fibrosis. [52] In line with the above reported data, it was observed in our study that administration of BLM increased the expression of ERK1/2 protein in experimental animals. Activated ERK levels were significantly reduced on treatment with sesamol as compared to BLM treated group (p < 0.001).…”
Section: Blm Induced Pulmonary Toxicity In Ratssupporting
confidence: 91%
“…Many authors have also reported that inhibition of ERK pathway leads to amelioration of pulmonary fibrosis. [52] In line with the above reported data, it was observed in our study that administration of BLM increased the expression of ERK1/2 protein in experimental animals. Activated ERK levels were significantly reduced on treatment with sesamol as compared to BLM treated group (p < 0.001).…”
Section: Blm Induced Pulmonary Toxicity In Ratssupporting
confidence: 91%
“…For big information such as fnancial accounting, simple classifcation methods can no longer meet the needs of users. Terefore, some scholars give a classifcation method according to the information labeling in the relational database to carry out labeling and classifcation so as to facilitate the public search, compared with traditional classifcation [17]. Te advantages and disadvantages of crowd classifcation are shown in Table 4.…”
Section: Categorizationmentioning
confidence: 99%
“…Emerging evidence suggests that an upregulated inflammatory response and abnormal metabolism of specific lipid molecules play significant roles in the formation, rupture and subsequent development of ACS. In addition to established traditional lipid biomarkers, such as low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C) and triglycerides (TGs), several metabolomic and lipidemic indicators, including ceramides and apolipoproteins, have been implicated in the occurrence and progression of ACS [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%